Short Bowel Syndrome: Intestinal Adaptation and Medical Therapy - WD Buie; OG Thurston; Richard N Fedorak (Canadian Journal of Gastroenterology)
Short bowel syndrome is a clinical entity, a consequence of significant loss of intestinal surface area, and manifests a variable picture of diarrhea, steatorrhea, malabsorprion and weight loss. Previously high mortality rates have been reduced by the early use of parenteral nutrition and have subsequently resulted in increased survival and prevalence of the condition. Ultimate patient survival is dependent on the intrinsic adaptive ability of residual intestine and this, in turn, is dependent upon length, type, functional state and the presence or absence of an ileocecal valve. The mechanisms of intestinal adaptation are not entirely understood; however, they can be grouped into three broad categories: luminal nutrition, hormonal factors, and pancreaticobiliary secretion. Medical treatment of short bowel syndrome remains supportive and centres around the control of three pathophysiological defects: decreased intestinal transit time, gastric hypersecretion, and reduced functional mucosal surface area.